The Investigation Propolis Foraging Preference of Different Honey Bee Races - (:unkn) unknown (My University, 2021)
In this study, it was investigated whether different bee breeds prefer_x000D_ different plant sources to collect propolis. For this purpose four different honey_x000D_ bee race (Apis mellifera caucasica, A. m. carnica, A. m. syriaca and A. m._x000D_ anatoliaca) naturally have been in Turkey were placed in the same isolated apiary;_x000D_ and Propolis was harvested from these races. chemical contents of alcoholic_x000D_ extractions of the harvested propolis were were analyzed by liquid_x000D_ chromatography-tandem mass spectrometry (LCMS / MS). In addition that, the_x000D_ pollen content of the same propolis samples were determined with a microscope._x000D_ According to the LCMS / MS results the propolis samples collected by different_x000D_ honey bee race differed significantly in terms of quercetin and ferulic acid. Data_x000D_ obtained from polen analyses revealed that Fabaceae and Apiaceae (PD >45%)_x000D_ families were mostly detected in propolis samples obtained from different races._x000D_ Although the polen from the Campanulaceae family was dedected only in the_x000D_ propolis samples from A. m. anatoliaca race, thr polen from Caryophyllaceae_x000D_ family was found in other propolis samples collected by A. m caucasica races. The_x000D_ results of this study showed that different honey bee races tend to different plant_x000D_ sources and the content of propolis may differ according to the bee races.

Bu çalışmada farklı arı ırklarının propolis toplamak için farklı bitki_x000D_ kaynaklarını tercih edip etmediği araştırılmıştır. Bu amaçla Türkiye’de doğal_x000D_ olarak bulunduğu bilinen 4 farklı bal arısı ırkı (Apis mellifera caucasica, A. m._x000D_ carnica, A. m. syriaca and A. m. anatoliaca) izole edilmiş aynı arılığa_x000D_ yerleştirilmiş ve bu ırklardan propolis hasadı yapılmıştır. Hasat edilen_x000D_ propolislerin alkolik ekstraksiyonları yapılarak sıvı kromatogram kütle_x000D_ spektrofotometrisi (LCMS/MS) ile kimyasal içerikleri analiz edilmiştir. Aynı_x000D_ zamanda aynı propolislerin mikroskop ile polen içeriği belirlenmiştir. Elde edilen_x000D_ sonuçlara göre farklı bal arısı ırklarının topladığı propolisler kuersetin ve ferulik_x000D_ asit bakımından önemli düzeyde farklılık göstermiştir. Farklı ırklardan elde edilen_x000D_ propolis örneklerinde en fazla Fabaceae and Apiaceae (PD >45%) familyasından_x000D_ polenlere reslanırken, Campanulaceae familyasından polene yalnızca A. m._x000D_ anatoliaca ırkının topladığı polenlerde ve Caryophyllaceae familyasından_x000D_ polenlere ise sadece A. m. caucasica ırkının topladığı propolislerde raslanmıştır._x000D_ Bu çalışmanın sonuçları farklı arı ırklarının farklı bitki kaynaklarına yönelme davranışında bulunduğunu ve ırka göre propolis içeriğinin değişebileceğini_x000D_ göstermiştir.
Farklı Bal Arısı Irklarının Propolis Toplama Tercihlerinin Araştırılması